Motor Dysfunctions and Neuropathology in Mouse Models of Spinocerebellar Ataxia Type 2: A Comprehensive Review - Alves-Cruzeiro, João M. Da Conceição; Mendonça, Liliana; Pereira de Almeida, Luís; Nóbrega, Clévio (Frontiers in Neuroscience, 2016)
Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant ataxia caused by an expansion of CAG repeats in the exon 1 of the gene ATXN2, conferring a gain of toxic function that triggers the appearance of the disease phenotype. SCA2 is characterized by several symptoms including progressive gait ataxia and dysarthria, slow saccadic eye movements, sleep disturbances, cognitive impairments and psychological dysfunctions such as insomnia and depression, among others. The available treatments rely on palliative care, which mitigate some of the major symptoms but ultimately fail to block the disease progression. This persistent lack of effective therapies led to the development of several models in yeast, C. elegans, D. melanogaster and mice to serve as platforms for testing new therapeutic strategies and to accelerate the research on the complex disease mechanisms. In this work, we review 4 transgenic and 1 knock-in mouse that exhibit a SCA2-related phenotype and discuss their usefulness in addressing different scientific problems. The knock-in mice are extremely faithful to the human disease, with late onset of symptoms and physiological levels of mutant ataxin-2, while the other transgenic possess robust and well-characterized motor impairments and neuropathological features. Furthermore, a new BAC model of SCA2 shows promise to study the recently explored role of non-coding RNAs as a major pathogenic mechanism in this devastating disorder. Focusing on specific aspects of the behavior and neuropathology, as well as technical aspects, we provide a highly practical description and comparison of all the models with the purpose of creating a useful resource for SCA2 researchers worldwide.